Carbonização hidrotérmica de resíduos de acerola (Malpighia emarginata D.C.): estudo de otimização, caracterização do hidrocarvão e aplicação - Nogueira, Geraldo Daniel Ribeiro (2020)
Fruit growing is a consolidated activity in Brazil, being this the third largest fruit producer in the world due to favorable climatic conditions. Acerola (Malpighia emarginata D.C.), for example, is a crop originating in Central America, but Brazil is its largest producer. This fruit is mainly consumed in the form of processed products due to its fragility. During processing there is a large generation of waste. Hydrothermal carbonization (HTC) appears as a promising technology aiming the reuse of these residues. HTC is a thermochemical process that converts biomass by applying high temperature in a suspension with subcritical water. This process simulates the natural coalification of biomasses and generates gaseous, liquid and solid products similar to fossil fuels. The solid products, also known as hydrochars, are carbonaceous materials and rich in oxygenated functional groups (OFG). The most varied applications for hydrochars are reported, such as: soil correction, solid fuel, and adsorption of environmental pollutants. The HTC of acerola residues and the hydrochar application were studied in this work, being presented in four stages. In the first one, the characterization of the acerola residue was carried out aiming thermochemical processes. In the second stage, the HTC of the acerola residue was studied using a fractional factorial design. The effects of process variables (temperature, reaction time, biomass / water ratio, pH of the feed water and stirring speed) on the solids yield (SY) and OFG of the hydrocarbon were evaluated. The liquid and solid products at the axial points were characterized in terms of composition and physical-chemical characteristics. Process optimization was also performed with the maximization of SY and OFG. The HCop was characterized in terms of its physical and chemical structure. In the third stage, the adsorption of the methylene blue dye in HCop was studied, being evaluated the influence of the temperature, the pH of the solution, the concentration of adsorbate and the concentration of adsorbent in the removal of methylene blue and in the capacity adsorption of HCop. In addition, studies of kinetics, equilibrium isotherms and thermodynamic analyzes were performed. Finally, the chemical activation of the hydrochar was carried out using potassium hydroxide as an activating agent. The activated hydrocarbon was characterized and its applicability in the adsorption of methylene blue was evaluated. The characterization of the acerola residue allowed us to conclude that this is a suitable material for thermoconversion processes, such as HTC. The results of the HTC study indicated that all the variables studied are significant in both responses (SY and OFG), being possible to obtain hydrochars with high SY and OFG. In the optimized conditions, HCop showed SY of 66.70% and 7.57 mmol/g of OFG. In assessing the applicability of HCop as a methylene blue adsorbent, it was observed that the adsorption, in this case, is spontaneous, endothermic and, probably, controlled by physisorption. The chemical activation was able to improve its surface area from 20.30 to 348.09 m²/g and increase the adsorption capacity by 7.18 times. Therefore, HTC is a promising technology for the sustainable modification of agro-industrial waste, aiming at its application as adsorbents of environmental contaminants.